Degradation of the Mechanical Properties and Hydrogen Generation in Cement Under Gamma Irradiation Assessed by Atomistic Simulation - AL Najjar, Omar (AUC Knowledge Fountain, 2024)
Although understanding the effect of the gamma-ray on cement-based materials is essential for many applications, such as the concrete contaminate of nuclear reactors or the storage of radioactive waste in cement-based waste forms, such understanding is still not fully developed. The importance of having such an understanding is becoming of utmost importance, especially with calls to extend the lifetime of nuclear power plants, and also due to some recent incidents of failures of the concrete structure in the nuclear fields. In this work, the details of preparing three molecular models as a representative structure of the main binding phase of cement-based materials, calcium-silicate-hydrate (C-S-H) are presented. These models have different Ca/Si ratios of 1.3, 1.5, and, 1.7. For a comparison purposes, The Tobermorite 14 Å which is a crystalline analogue of C-S-H with a Ca/Si=0.83 is included in this study. In addition, a full description regarding the procedure followed to simulate the irradiation events is given here. The gamma dose simulated in the work is up to11.9 MGy, which is equivalent to the gamma dose received by concrete containment of the light water reactor over 10 years. A semi-classical force field (REAXFF) has been adopted here due to its capability to capture the chemical reactions that are anticipated to happen during irradiation (bond breakage and formation). On the other hand, a classical force field (CSHFF) has been used for the calculation of the mechanical properties as CSHFF is capable of correctly describing the mechanical response of cement hydrates. By examining the structural and mechanical properties of the C-S-H before and after irradiation, a deterioration in the mechanical properties and a formation of H2 molecules are observed. Both effects are attributed to the status of water in the interlayer space of C-S-H. For example, water dissociation causes a reduction in the ultimate compressive strength of the C-S-H. This is because the dissociated water reduces the cohesion of the C-S-H by reducing the charge of the C-S-H layers. In addition to that, water dissociation is considered the first step towards hydrogen formation as it provides the precursor to form H2 molecule. On the other hand, water evaporation is shown to have a negative correlation with the young’s modulus. This is because water exists in the interlayer space acts as a bridging solid between the C-S-H layer. Moreover, by comparing the mechanical response of the different models upon irradiation, it revealed that the C-S-H with a C/S: 1.3 ratio is more suitable to be used for the concrete containment of the nuclear power plant as its loss of only 37.5% of its compressive strength. conversely, the C-S-H model with a C/S ratio of 1.7 is shown to be more appropriate for nuclear waste confinement applications as no hydrogen production is observed during the irradiation. This is attributed to the highly defective structure of the silicate chain which provides more active sites to attract the protons and that prevent hydrogen formation. The results of this work have a very important implication in describing the origin of the degradation in cement-based materials due to radiation exposure which is the first step towards the design of cement-based materials resistant to radiation damage.